Decoupling Representations and the Chain of Arguments - Santibáñez, Cristián (Informal Logic, 2021)
In this paper, I propose to understand argumentative decoupling—that is, the structural fact of the argumentative chain self-referring to one (or more) of its constituents (reason, data, conclusion, point of view) in subsequent arguments—as part of the way in which cognitive decoupling representation works. In order to support this claim, I make use of part of the discussion developed in cognitive studies and evolutionary theories that describes this phenomenon when explaining intentional communication. By using Toulmin’s model, I exemplify how decoupling representation may be seen as part of a chain of arguments in which a second argumentative move is usually oriented to action. I conclude by reflecting on the relationship between this human cognitive capacity and the problem of recursion to hold that these two concepts are not synonymous but stand in a subordinated and complementary relation to each other.